2019
DOI: 10.2298/psi181121009r
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, personality traits, and body image in Italian pre-adolescents: An opportunity for overweight prevention

Abstract: We investigated the relationship between body mass index (BMI) and personality traits, socioeconomic status (SES), and body image (BI) at the beginning of preadolescence. Data were collected from 238 Italian children aged 10-11 years using self-report scales. Information about SES was derived from parental education and professional status. BI was the variable the most strongly associated with BMI. Controlling for BI, SES, and gender, Agreeableness was inversely associated with BMI, whilst Extroversion was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 47 publications
(72 reference statements)
0
28
0
2
Order By: Relevance
“…Mindfulness has been defined as the awareness that arises by intentionally paying attention, in the present moment and in a non-judgmental way, to the flow of experience (Kabat-Zinn, 2003 ). Mindfulness is a theoretical instance that finds its implementation in a set of meditation and psycho educational exercises aimed at understanding certain fundamental themes such as stress, attachment and dependence on internal and external content and therefore the importance of subjective observation of thoughts, emotions, and physical sensations (Kabat-Zinn, 2009 ; Rosa et al, 2019 ). Mindfulness propensity is known as facilitators of well-being and adaptation for healthcare professionals, together with high adaptive defense mechanisms (Catalano et al, 2019 ; Di Giuseppe et al, 2019a , 2020a , c ; Martino et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness has been defined as the awareness that arises by intentionally paying attention, in the present moment and in a non-judgmental way, to the flow of experience (Kabat-Zinn, 2003 ). Mindfulness is a theoretical instance that finds its implementation in a set of meditation and psycho educational exercises aimed at understanding certain fundamental themes such as stress, attachment and dependence on internal and external content and therefore the importance of subjective observation of thoughts, emotions, and physical sensations (Kabat-Zinn, 2009 ; Rosa et al, 2019 ). Mindfulness propensity is known as facilitators of well-being and adaptation for healthcare professionals, together with high adaptive defense mechanisms (Catalano et al, 2019 ; Di Giuseppe et al, 2019a , 2020a , c ; Martino et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional distress could exist independently from such chronic disease, though considering the higher risk of mortality and morbidity due to diabetes, a psychological elaboration processing would be useful for the psychic integration of the chronic illness experience within patients' daily life (Whittemore et al, 2010;Castelnuovo et al, 2015;Van Houtum et al, 2015;Stanton and Hoyt, 2017;Di Giuseppe et al, 2018Savarese et al, 2018;Catalano et al, 2019a). Demographical and physical characteristics, such as body mass index (BMI) and smoking and alcohol consumption, could predict depression in Type 2 Diabetes Mellitus (T2DM) (Bouwman et al, 2010;Rosa et al, 2019). Smith et al (2013) observed a significant correlation between diabetes, anxiety symptoms and anxiety disorders, and highlighted that a fruitful psychological adjustment to diabetes is significantly associated with a better metabolic control, self-care and higher QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis by Rodgers et al (36) indicated a significant effect sizes of exposure to pro-eating disorder websites on body image dissatisfaction, negative affect, and diet. Rosa et al (37) indicated that body image was the strongly associated with body mass index (BMI). However, the authors did not notice the difference according to gender among studied 238 Italian children aged 10-11 years old.…”
Section: Introductionmentioning
confidence: 99%